The perceived costs and benefits of mentoring college students with intellectual disability on stereotype consistent and inconsistent tasks. Issue 8 (29th June 2022) - McManus, J. L.; Reed, C.; Saucier, D. A.
Abstract: Background: According to the stereotype content model, individuals with intellectual disability are perceived as having greater warmth‐related traits (e.g. sociable and humorous) and fewer competence‐related traits (e.g. independence and intelligence). Methods: We examined college students' perceived costs and benefits of mentoring peers with intellectual disability on stereotype‐consistent (i.e. socially oriented) or inconsistent (i.e. academically oriented) tasks. Participants read about peer mentoring programmes that helped college students with or without intellectual disability on socially or academically oriented tasks before reporting their perceived costs and benefits of peer mentoring. Results: Mentoring students with intellectual disability was associated with greater benefits (i.e. connectedness between mentors and students, student utility and mentor benefits) on academically oriented tasks but greater costs for mentors on socially oriented tasks. Additionally, participants reported that they would experience greater positive feelings if they were to mentor a student with an intellectual disability. However, the perceived benefits to the student and some costs (i.e. discomfort, paternalism and costs to student) were not influenced by whether the student had an intellectual disability and the type of mentoring task. Discussion: Results indicate individuals find greater rewards working with individuals with intellectual disability on stereotype‐inconsistent tasks and offer suggestions for postsecondary education peer mentoring programmes.